2009
DOI: 10.1007/s00431-009-1100-3
|View full text |Cite
|
Sign up to set email alerts
|

Three familial cases of drug-resistant Mycoplasma pneumoniae infection

Abstract: Our clinical and laboratory observations strongly support the idea that the host immune maturity, rather than a virulence factor of the organism, is a major determinant factor of disease severity of M. pneumoniae infection and that drug resistance does not necessarily lead to a serious clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The positivity rate of NPA specimens in the same period from November 2007 to March 2009 in all pneumonia children in our hospital was 16.9% (1,246 in 7,381 cases, data not published). The immunopathogenesis of M. pneumoniae pneumonia is considered to be age-dependent [10]. In our study, children with MPP were older than non-MPP, which is also in agreement of other studies [3,6,11,19,23].…”
Section: Discussionsupporting
confidence: 94%
“…The positivity rate of NPA specimens in the same period from November 2007 to March 2009 in all pneumonia children in our hospital was 16.9% (1,246 in 7,381 cases, data not published). The immunopathogenesis of M. pneumoniae pneumonia is considered to be age-dependent [10]. In our study, children with MPP were older than non-MPP, which is also in agreement of other studies [3,6,11,19,23].…”
Section: Discussionsupporting
confidence: 94%
“…Second, a previous study showed a gender difference in treatment outcomes for pneumonia ( 23 ). Meanwhile, the immunopathogenesis of MPP is regarded as age-dependent ( 24 ). Age may be the sole predisposing factor of MPP ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…[1,2] In recent years the incidence of M. pneumoniae pneumonia (MPP) has risen, and reports on macrolide-resistant M. pneumoniae have been increasing. [3,4] Refractory or critical MPP cases are also seen increasingly, with a great harm to children, especially those with weak immune function. climate effects.…”
Section: Introductionmentioning
confidence: 98%